دور المغذيات في نمو العوالق النباتية في المياه الشاطئية لمدينة اللاذقية - سليمان, نوار; درويش, فيروز (Latakia University Journal -Biological Sciences Series, 2019)
تم في هذا البحث دراسة سلوكية العوالق النباتية ضمن تجارب ميزوكوزمية لإيضاح التغيرات الحاصلة في نموها تحت تأثير تراكيز مختلفة من المغذيات (NO ، PO ، SiO )، باستخدام مياه بحر طبيعية غير مرشحة، جمعت من ثلاث محطات بحرية مختلفة بخصائصها البيئية خلال شهر حزيران 2010، تم خلالها دراسة كمية المغذيات المستهلكة من قبل العوالق النباتية وتغيرات الكلوروفيل a وتحديد التركيب النوعي للعوالق النباتية. أدى تغيير تراكيز المغذيات في تجارب الإغناء إلى تحريض نمو العوالق النباتية في جميع الأوساط المستخدمة في دراستنا، وبشكل خاص لدى رفع المغذيات مرتين على تراكيزها الطبيعية في مصب النهر الكبير الشمالي، حيث بلغت القيمة العظمى لتراكيز الكلوروفيل a خلال الأسبوع الأول من الحضن (Max Chl a=57.2 ملغ.م-3)، ترافق ذلك مع استهلاك كامل لجميع المغذيات في نهاية التجارب. لم تستطع ثنائيات السياط أن تنافس المشطورات في الحصول على المغذيات المتاحة في الوسط، وكانت المشطورات الأسرع في استهلاك المغذيات حيث سادت الأنواع: Chaetoceros didymus، Pseudo-nitzschia delicatissima وThalassiosira rotula. In this study, we investigate phytoplankton behavior applying Mesocosm experiments to clarify the changes in their growth under different nutrients concentrations (e.g. NO , PO , SiO ). Using unfiltered seawater, the samples were collected from three different marine stations during June 2010. The amount of nutrients consumed by phytoplankton was studied, the Chl a changes were identified and the specific composition of phytoplankton was determined. Changing nutrients concentrations instigated phytoplankton growth, particularly during doubling the initial concentrations in Al-Kabir Al-Shimali river estuary. The maximum value of Chl a was observed during the first week after incubation (Max Chl a = 57.2 mg.m-3), and this was coincided with complete consumption of all nutrients at the end of experiments. Dinoflagellates couldn’t compete with diatoms in having the nutrients available in situ, as diatoms were faster in nutrients consumption, and the following species dominated: Chaetoceros didymus, Pseudo-nitzschia delicatissima & Thalassiosira rotula.